Modified artificial graphite negative electrode active material as well as preparation and application thereof
By using biomass oil to perform two-stage calcination treatment after graphitization, the physical and chemical structure and conductivity of graphite are optimized, and the problem that existing graphite cladding materials are difficult to take into account both high fast charging and high capacity is solved, and the performance improvement of 4~6C fast charging in lithium-ion batteries is achieved.
Patent Information
- Application Number
- CN202510057634.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Existing graphite clad materials are difficult to take into account high fast charging and high capacity performance, especially in lithium-ion batteries, which cannot meet the needs of 4~6C fast charging.
By heat-treating the coke raw material at a specific temperature and graphitizing the two-stage calcination treatment with the assistance of biomass oil, the physical and chemical structure and electrical conductivity of graphite are optimized and the ion and electron conduction network is improved.
The prepared modified graphite material can take into account excellent capacity, fast charging and high temperature stability, significantly improving the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119911900A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular to the field of graphite. Background Art
[0002] Since the invention of the first BLC-2 battery in the 1990s, graphite carbon and its derived composite materials have been the mainstream negative electrode materials for lithium-ion batteries in the past three decades. In the traditional lithium-ion battery configuration based on graphite anode, the positive electrode material is generally considered to be the key factor affecting the energy density, while the negative electrode material is usually related to the rate performance or power density of the battery. The existing modification method of mixing asphalt with graphite can usually only achieve a 2C charging capacity. Improving the fast charging performance of commercial graphite negative electrodes is crucial to the commercialization of lithium-ion batteries.
[0003] In order to improve the performance of the battery, the main means of the prior art is to carbon-coat the graphite material. For example, the Chinese patent document with publication number CN107814382A discloses a modified natural graphite negative electrode material and its preparation method and use. Specifically, the natural graphite powder and asphalt are impregnated with a hot isostatic press to fully ensure that the asphalt fills the pores inside the graphite particles under high temperature and high pressure, and at the same time forms an asphalt coating layer on its surface. After graphitization, the artificial graphite is in-situ embedded in the natural graphite and the surface of the modified natural graphite negative electrode material with a core-shell structure is obtained. The filling rate of artificial graphite in the natural graphite pores is ≥94%, the particle surface is smooth, and the sphericity is high. The modified natural graphite negative electrode material obtained by the invention has an initial coulomb efficiency of ≥96%, and a capacity retention rate of ≥80% after 1500 cycles at room temperature 1C.
[0004] For another example, the Chinese patent document with publication number CN106486653A discloses a liquid-coated modified graphite negative electrode material and a preparation method thereof, which is prepared from 800 to 1200 parts of graphite fine powder and a liquid coating agent, and the graphite fine powder and the liquid coating agent are mixed in a high-speed mixer with heat preservation and heating at high speed, and then added to a continuous coating machine for coating to obtain a precursor, and then subjected to high-temperature heat treatment in a tubular furnace under the protection of inert gas, heat preservation, and cooling to room temperature to obtain a liquid-coated modified graphite negative electrode material. This technology coats the graphite negative electrode with asphalt. After testing, the rate performance of this patent is only 2~3C, which cannot meet the market demand of 4~6C.
[0005] In summary, existing conventional graphite composite materials are difficult to meet the requirements of high-rate fast charging applications. In addition, it is difficult to take into account both high fast charging and capacity performance requirements. Summary of the invention
[0006] In view of the problem that existing graphite coated materials are difficult to achieve both fast charging and high capacity, the first purpose of the present invention is to provide a method for preparing modified graphite, aiming to prepare a graphite modified material that achieves both excellent fast charging and high capacity.
[0007] The second purpose of the present invention is to provide modified graphite obtained by the preparation method and its application.
[0008] A third object of the present invention is to provide a secondary battery comprising the modified graphite.
[0009] A method for preparing modified graphite, comprising pre-heating a coke raw material at a temperature T1, and then performing a graphitization treatment to obtain a graphite material; then mixing the graphite material with biomass oil, and pre-calcining the first stage at a temperature T2, and then performing a second stage of calcination at a temperature T3 to obtain; The temperature T1 is 500-800°C; The temperature T2 is 500-800°C; The temperature T3 is 1000-1500°C; The biomass oil is at least one of waste cooking oil, acidified oil, sewage oil, palm oil, rapeseed oil and soybean oil, and / or a fraction collected from carbonization of biomass raw materials; the biomass raw materials include at least one of bamboo, straw and bagasse.
[0010] The present invention innovatively graphitizes the coke raw material after heat treatment at temperature T1, and then performs a subsequent two-stage roasting treatment with the assistance of the special biomass oil. This can achieve synergy, make full use of the composition and physical characteristics of the biomass oil, optimize the physical and chemical structure of graphite, improve the storage capacity of active ions, and also construct an efficient ion and electron conduction network to improve the conduction efficiency. In this way, a graphite material with excellent capacity, fast charging and high-temperature stability can be prepared.
[0011] In the present invention, the coke raw material comprises at least one of petroleum coke, isotropic coke, needle coke, shot coke and sponge coke; In the present invention, the particle size of the coke raw material is controlled to be 7-10 μm (particle size after powdering).
[0012] In the present invention, the atmosphere of the heat treatment is a protective atmosphere; Preferably, the holding time at temperature T1 is 3 to 10 h.
[0013] Preferably, the particle size of the material after heat treatment is controlled to be 5-15 μm before graphitization treatment.
[0014] In the present invention, the graphitization temperature is above 2600°C, preferably 2800-3300°C; Preferably, the graphitization time is 10 to 30 h.
[0015] In the present invention, the combination of the components in the biomass oil from a special source can optimize the physical and chemical structure of the material, and can further optimize the electrochemical properties such as fast charging of the prepared modified graphite material.
[0016] In the present invention, the biomass oil is a fraction (biomass oil) collected by carbonization of bamboo and / or bagasse; preferably, the weight ratio of bamboo-based biomass oil to sugarcane-based biomass oil is 1:0.5-2. Studies have shown that the preferred biomass oil can further benefit its physical and chemical characteristics and further optimize the fast charging and high temperature performance of modified graphite.
[0017] The carbonization temperature is 400~600℃.
[0018] Preferably, the preparation steps of biomass oil are: subjecting the biomass raw material to carbonization treatment to obtain biomass crude oil, and subjecting the biomass crude oil to fractionation, hydrogenation, alkali solution treatment, acid solution treatment, water washing, and dehydration treatment to obtain the biomass crude oil.
[0019] In the present invention, the biomass oil can be collected in a conventional manner, for example, the carbonized tail gas can be passed into a condensing device to collect the biomass oil therein.
[0020] In the present invention, the weight ratio of the graphite material to the biomass oil is 100:3-8.
[0021] Temperature T2 is 600~700℃.
[0022] In the present invention, the first stage calcination time is 0.5 to 2 hours, and can further be 1 to 1.5 hours.
[0023] Temperature T3 is 1200~1400℃.
[0024] Preferably, the second calcination time is 2 to 6 hours.
[0025] The invention also provides modified graphite obtained by the preparation method.
[0026] The preparation method described in the present invention can give the prepared material special physical and chemical characteristics, and the material with the physical and chemical characteristics can take into account excellent capacity, fast charging and high temperature performance.
[0027] The present invention also provides an application of the modified graphite prepared by the preparation method, which is used as a negative electrode active material to prepare a secondary battery.
[0028] In the present invention, based on existing principles and means, the modified graphite of the present invention can be used as a negative electrode active material to prepare a desired secondary battery.
[0029] The secondary battery of the present invention may be an alkali metal ion battery, such as a sodium ion battery or a lithium ion battery.
[0030] The present invention also provides a secondary battery, characterized in that it comprises the modified graphite prepared by the preparation method of the present invention.
[0031] The secondary battery of the present invention, except for the modified graphite of the present invention, may have conventional components and parts.
[0032] Beneficial Effects The present invention innovatively graphitizes the coke raw material after heat treatment at temperature T1, and then performs a subsequent two-stage roasting treatment under the compounding of biomass oil. This can optimize the microstructure of the graphite, control parameters such as the lattice structure, defects and pore structure of the graphite, and optimize its electrical conductivity and ion diffusion performance, thereby improving the capacity, fast charging and high temperature performance of the prepared material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the modified graphite material finally obtained in Example 1.
[0034] Figure 2 This is the specific capacity diagram of the final modified graphite material of Example 1; Figure 3 These are high-magnification images of Example 1, Comparative Example 1 and Comparative Example 3. DETAILED DESCRIPTION
[0035] Aiming at the demand that graphite negative electrode materials in the current market cannot be fast charged at 4~6C under the condition of lithium-ion batteries, a preparation method of biomass oil liquid phase coated modified artificial graphite negative electrode material is proposed, and the process steps and conditions are as follows: ① petroleum coke is roughly crushed to micron level ② raw materials are treated at high temperature of 500~800℃ ③ powdering to 5~15μm ④ high temperature graphitization treatment at 3000℃ to obtain a precursor ⑤ the graphite fine powder obtained from the precursor and biomass oil are put into one of the kneading / mixing / fusion equipment for kneading for 5~20min ⑥ fully kneaded into a high temperature heating coating kettle for 500~800℃ coating ⑦ high temperature carbonization at 1200℃ in a tubular furnace to obtain the product.
[0036] The petroleum coke used is a coke product obtained by separating light and heavy oils through distillation of crude oil and then thermal cracking of heavy oil. Its indicators are moisture ≤ 10%, S content 0.5~4.0, and volatile matter = 1.0~11.0%.
[0037] Biomass oil is produced by pyrolysis of plants in the absence of air to generate biochar and mixed liquid. After the mixed liquid is left to stand, the clear liquid on top is vinegar, and the black viscous liquid below is biomass oil. The unique molecular structure and carbonization characteristics of the biomass oil can introduce certain microstructure regulation in the preparation process of carbon materials. By controlling the parameters such as the lattice structure, defects and pore structure of carbon materials, its conductivity and ion diffusion performance can be optimized, thereby improving the fast charging performance of graphite negative electrode materials. Its indicator coking value = 10~20%, ash content <0.1.
[0038] In the following cases, the biomass oil is prepared by the following steps, for example: Step 1. Raw material preparation and pretreatment Raw material selection: Place biomass (wood, agricultural residues) in a carbonization furnace, carbonize at a temperature of 500±20℃ and nitrogen, collect and cool the gas phase fraction components in the carbonization stage to obtain biomass crude oil; Step 2. Fractionation Heating fractionation: The crude biomass oil is heated for fractionation, and the fractions in the temperature range of 250~300℃ are collected: Step 3. Catalytic Hydrotreating The fraction of step 2 is hydrogenated using a hydrogenation catalyst, wherein the hydrogenation catalyst is a nickel-based, molybdenum-based, Pd-based catalyst, etc., and the hydrogenation process is: at 300~450°C and 1~5 MPa pressure conditions, hydrogen is introduced for hydrogenation reaction for 1~2 hours.
[0039] 4. Acid-base neutralization The components after hydrogenation in step 3 are treated with alkali solution (sodium hydroxide with a concentration of 0.5-1M) in advance, and then treated with acid solution (dilute sulfuric acid with a concentration of 0.5-1M), and then washed with water; 5. Dehydration and removal of impurities The bio-oil in step 4 is dehydrated and filtered to obtain biomass oil.
[0040] Example 1 Step 1: The petroleum coke is crushed by a jaw crusher and placed in a nitrogen atmosphere, and heat-treated in a muffle furnace at 600°C (carbonization temperature) for 5-6 hours to obtain a treated raw material; the treated raw material is powdered and graded to particles of 7-10 μm; and then graphitized at 3000°C (graphitization temperature) for 20±0.5 hours to obtain graphite carbon; Step 2: Graphite carbon and biomass oil (biomass oil from bamboo, the preparation method is as above, the weight ratio of graphite carbon to biomass oil is 100:5) are put into a kneading / mixing / fusion equipment for 10-15 minutes, followed by a first calcination at 600°C in a nitrogen atmosphere (time is 1 hour); then the temperature is raised to 1200°C for a second calcination (time is 4 hours) to obtain the required modified graphite material.
[0041] Example 2 Compared with Example 1, the only difference is that the biomass oil is changed. The experimental groups are: Group A: biomass oil is acidified oil; Group B: biomass oil is biomass oil collected by carbonizing sugarcane bagasse (preparation method is the same as above, except that the biomass is sugarcane bagasse); Other operations and parameters are the same as in Example 1.
[0042] Example 3 Compared with Example 1, the only difference is that the processing atmosphere in step 1 is replaced by Ar, in step 1, the carbonization temperature is 750°C, and the graphitization temperature is 3100°C; in step 2, the weight ratio of graphite carbon to biomass oil is 100:7; the temperature of the first calcination stage is 700°C, and the time of the first calcination stage is 1.5h; the temperature of the second calcination stage is 1400°C, and the time of the second calcination stage is 2.5h, and other operations and parameters are the same as in Example 1.
[0043] Example 4 The difference from Example 1 is that the biomass oil is the biomass oil of Example 1 and the biomass oil of Example 2B in a weight ratio of 1:1. Other operations and parameters are the same as those in Example 1.
[0044] Comparative Example 1 Compared with Example 1, the only difference is that the biomass oil is the biomass oil collected by carbonizing sawdust, and the other operations and parameters are the same as Example 1.
[0045] Comparative Example 2 Compared with Example 1, the only difference is that in step 2, no biomass oil is added, and other operations and parameters are the same as in Example 1.
[0046] Comparative Example 3 Compared with Example 1, the only difference is that step 2 is not performed, and other operations and parameters are the same as Example 1.
[0047] Capacity: Button battery preparation method: Add binder, conductive agent and solvent to graphite composite material, stir and mix to make slurry, apply the obtained slurry on copper foil, dry and roll to make button battery. The binder is LA132 binder, the conductive agent is conductive agent SP, and the solvent is double distilled water; and the weight ratio of graphite composite material, conductive agent SP, LA132 binder and double distilled water is: 98:1:4:220.
[0048] Using lithium metal sheets as electrodes, composite films of polyethylene (PE), polypropylene (PP) and polyethylene propylene (PEP) as separators, and LiPF6 / EC+DEC (1:1) as electrolyte, simulated battery assembly was performed in an argon-filled glove box. The prepared button cells were installed in the Wuhan Blue Point CT2001A battery tester and charged at a rate of 0.1C. The charge and discharge voltage range was 0.005V to 2.0V. The first discharge capacity was measured as shown in Table 1.
[0049] According to the national standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", the graphitization degree, specific surface area and powder OI value of the above-mentioned anode materials were tested as shown in Table 1: Cyclic expansion test: Negative electrode formula C (active material, materials prepared in each case): SP: CMC: SBR = 95.8: 1: 1.2: 2. Positive electrode formula LFP (lithium iron phosphate): SP: PVDF = 96: 2: 2. At 25 ± 2 ° C, after 50 cycles of 0.5C constant current constant voltage charging (cut-off voltage 3.65V) and 0.5C constant current discharge (cut-off voltage 2.5V), the battery thickness change was measured and the expansion rate was calculated to evaluate its structural stability.
[0050] 60℃ cycle life test: Negative electrode formula C (active material, materials prepared in each case): SP:CMC:SBR=95.8:1:1.2:2 Positive electrode formula LFP:SP:PVDF=96:2:2 Under 60±2℃ environment, after 50 cycles of 0.5C constant current and constant voltage charging (cut-off voltage 3.65V) and 1C constant current discharge (cut-off voltage 2.5V), the capacity retention rate was tested.
[0051] Storage at 60℃ (7d) Retention rate (%) / Recovery rate (%): Negative electrode formula C (active material, materials prepared in each case): SP:CMC:SBR= 95.8:1:1.2:2 Positive electrode formula LFP:SP:PVDF=96:2:2 Under 25±2℃ environment, charge with 0.5C constant current and constant voltage (cut-off voltage 3.65V), discharge with 0.5C constant current and record the capacity before storage C0 (cut-off voltage 2.5V), fully charge with constant current and constant voltage, and then store at 60℃ for 7d, discharge with 0.5C constant current and record the capacity to maintain C1 (cut-off voltage 2.5V), then fully charge with constant current and constant voltage, and then discharge with 0.5C constant current and record the capacity to recover C2 (cut-off voltage 2.5V), retention rate: C1 / C0; recovery rate C2 / C0.
[0052] In the full battery system of the cycle test, the model can be CR2025; the separator is Celgard 2320, and the electrolyte is 1M LiPF6 in EC / DEC / DMC (1:1:1).
[0053]
[0054] Rate performance data see Figure 3 .
[0055] It can be seen from Example 1 that through the unique combination of biomass oil, certain microstructural regulation can be introduced in the preparation process of carbon materials. By controlling parameters such as the lattice structure, defects and pore structure of carbon materials, its ion diffusion performance can be optimized. Examples 2A and 2B maintain the same improved performance as Example 1. In Example 3, the OI value of the sample is further reduced to 3.54, the fast charging performance is improved, and the more uniform coating layer helps to form a thin coating layer to improve the fast charging performance. The capacity is the same as that of Case 1, and the uniform and thin carbon layer wraps the pore structure on the graphite surface to reduce the specific surface area. In Example 4, by mixing the biomass oil and the biomass oil of Example 2B, better material properties and electrochemical properties are shown. This is because the decomposition process of the two biomass oils may produce complementary carbon sources, which can form a more uniform and dense carbon coating on the graphite surface. This not only improves the conductivity of graphite, but also provides better structural stability during the charging and discharging process.
Claims
1. A method for preparing modified graphite, characterized in that: The coke raw material is pre-heated at a temperature T1, and then graphitized to obtain a graphite material; the graphite material and biomass oil are then mixed, and pre-calcined at a temperature T2 for a first stage, and then calcined at a temperature T3 for a second stage, to obtain; The temperature T1 is 500-800°C; The temperature T2 is 500-800°C; The temperature T3 is 1000-1500°C; The biomass oil is at least one of waste cooking oil, acidified oil, sewage oil, palm oil, rapeseed oil and soybean oil, and / or a fraction collected from carbonization of biomass raw materials; the biomass raw materials include at least one of bamboo, straw and bagasse.
2. The method for preparing modified graphite according to claim 1, characterized in that: The coke raw material comprises at least one of petroleum coke, isotropic coke, needle coke, shot coke and sponge coke; Preferably, the particle size of the coke raw material is controlled to be 7-10 μm.
3. The method for preparing modified graphite according to claim 1, characterized in that, The atmosphere of the heat treatment is a protective atmosphere; Preferably, the holding time at temperature T1 is 3 to 10 h; Preferably, the particle size of the material after heat treatment is controlled to be 5-15 μm before graphitization treatment.
4. The method for preparing modified graphite according to claim 1, characterized in that, The graphitization temperature is above 2600°C, preferably 2800-3300°C; Preferably, the graphitization time is 10 to 30 h.
5. The method for preparing modified graphite according to claim 1, characterized in that, The biomass oil is a fraction collected by carbonization of bamboo and / or sugarcane bagasse; preferably, the weight ratio of bamboo-based biomass oil to sugarcane-based biomass oil is 1:0.5-2; Preferably, the carbonization temperature is 400-600°C; Preferably, the preparation steps of biomass oil are: subjecting the biomass raw material to carbonization treatment to obtain biomass crude oil, and subjecting the biomass crude oil to fractionation, hydrogenation, alkali solution treatment, acid solution treatment, water washing, and dehydration treatment to obtain the biomass crude oil.
6. The method for preparing modified graphite according to claim 1 or 5, characterized in that: The weight ratio of the graphite material to the biomass oil is 100:3-8.
7. The method for preparing modified graphite according to claim 1 or 5, characterized in that: The first stage of roasting time is 0.5~2h; Preferably, the second calcination time is 2 to 6 hours.
8. A modified graphite obtained by the preparation method according to any one of claims 1 to 7.
9. An application of modified graphite obtained by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as negative electrode active material to prepare secondary batteries.
10. A secondary battery, characterized in that: The modified graphite comprises the modified graphite obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Liquid-phase coated and modified graphite negative electrode material and preparation method therefor
CN106486653A
Long-life modified natural graphite cathode material as well as preparation method and use thereof
CN107814382A
Method for preparing charcoal by using straw
CN103627418A
Waste negative electrode-based regenerated graphite material as well as preparation and application thereof
CN115432699A
Artificial graphite material, preparation thereof and application of artificial graphite material in lithium secondary battery
CN115536019A